2011
DOI: 10.1074/jbc.m110.179028
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of Ca2+-CIB1 and Mg2+-CIB1 and Their Interactions with the Platelet Integrin αIIb Cytoplasmic Domain

Abstract: The calcium-and integrin-binding protein 1 (CIB1) is a ubiquitous Ca 2؉ -binding protein and a specific binding partner for the platelet integrin ␣IIb cytoplasmic domain, which confers the key role of CIB1 in hemostasis. CIB1 is also known to be involved in apoptosis, embryogenesis, and the DNA damage response. In this study, the solution structures of both Ca 2؉ -CIB1 and Mg 2؉ -CIB1 were determined using solution-state NMR spectroscopy. The methyl groups of Ile, Leu, and Val were selectively protonated to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 57 publications
2
42
0
Order By: Relevance
“…Therefore, an amino acid change at p.Arg66 would likely destabilize the interaction with integrin and thus attenuate integrin activation (Figures 4a and b). 22,34 In consistence with our calcium-imaging data, Arg66 is located away from the Ca 2+ binding pockets, 20,21 and thus the substitution of tryptophan for arginine at position 66 is predicted not to alter calcium-buffering abilities of CIB2. Similarly, the substitution of serine for phenylalanine at position 91 is also predicted to weaken the interaction of CIB2 with αIIβ integrin.…”
Section: B and C But Not Isoforms A And Cib2-006 (Supplementarymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an amino acid change at p.Arg66 would likely destabilize the interaction with integrin and thus attenuate integrin activation (Figures 4a and b). 22,34 In consistence with our calcium-imaging data, Arg66 is located away from the Ca 2+ binding pockets, 20,21 and thus the substitution of tryptophan for arginine at position 66 is predicted not to alter calcium-buffering abilities of CIB2. Similarly, the substitution of serine for phenylalanine at position 91 is also predicted to weaken the interaction of CIB2 with αIIβ integrin.…”
Section: B and C But Not Isoforms A And Cib2-006 (Supplementarymentioning
confidence: 99%
“…Molecular modeling suggests impaired interaction of CIB2 with effector molecules due to the c.196C4T and c.272T4C variants When modeled using the known crystal structure of CIB1 as backbone 4,21,34 in CIB2, the p.Arg66 maps to the N-terminal domain of CIB2 within a region that has been implicated in the interaction of CIB protein with the carboxy terminal, unstructured, negatively charged tail of αIIβ integrin. CIB1 is involved in the activation of integrin αIIβ3.…”
Section: B and C But Not Isoforms A And Cib2-006 (Supplementarymentioning
confidence: 99%
“…NMR residual dipolar couplings take advantage of the restriction on the molecular tumbling introduced by anisotropic media to address the relative orientation of secondary structural elements inside proteins (45). Hence, RDCs were measured for the apo and holo forms of the protein in the presence of phage pf1 (45,46). Also, model structures of the N-lobe and C-lobe of OsCaM61 were created from available mCaM structures (apo N-lobe from Protein Data Bank code 1CFD, apo C-lobe from Protein Data Bank code 1CFD, holo N-lobe from Protein Data Bank code 1J7O, and holo C-lobe from Protein Data Bank code 1J7P) using the SWISS-MODEL server (Fig.…”
Section: Oscam61 Cam Domain and Cte Structural Characteristics-mentioning
confidence: 99%
“…As we known, structure determines function. To get insight into the function of CIB1, the structure of CIB1 has been explored extensively by sequence analysis, nuclear magnetic resonance spectroscopy (NMR), circular dichroism or X-ray crystallography [6-8, 10, 80]. Thus, we believed that along with the further analysis of CIB1 structure, more and more CIB1 partners and the precise mechanisms for multiple function of CIB1 will be identified in the future.…”
Section: Cib1 and Other Pathological Or Physiological Processmentioning
confidence: 99%
“…Yamniuk et al identified that low affinity Ca 2+ binding events that influence the structures of the N- and C-terminal extensions of CIB1 under high Ca 2+ crystallization conditions [10]. Studies suggested that Mg 2+ -CIB1 and Ca 2+ -CIB1 exhibit a more ordered 4-EF-hand structure with smaller hydrodynamic radius than a highly flexible molten globule-like CIB1 (not bound to any metals)[6, 8]. A consensus sequence 5’-MGXXXS/T-3’ at the CIB1 N terminus appears to be crucial for its myristoylation modification and plasma membrane localization [4, 7, 13, 14].…”
Section: Introductionmentioning
confidence: 99%